The root of the matter: Linking root traits and soil organic matter stabilization processes. (May 2018) - Poirier, Vincent; Roumet, Catherine; Munson, Alison D.
Abstract: Plant roots contribute substantially to the formation of stable soil organic matter (SOM), and there is evidence that species differ in their contribution to SOM stabilization. However, it remains unclear what specific root traits contribute to the three SOM stabilization mechanisms: recalcitrance against decomposition, occlusion in soil aggregates and interaction with soil minerals and metals. This is likely because research is highly fragmented and hampered by disciplinary barriers. By reviewing both plant functional ecology and soil science literature, we identified 18 different traits: architectural, morphological, physiological, symbiotic and chemical root characteristics, influencing the three SOM stabilization mechanisms. We found that traits increasing root recalcitrance promote short term stabilization by slowing decomposition, but that traits reducing recalcitrance contribute to long term stabilization by reaction of microbial products with mineral surfaces. Root length density, mycorrhizal association and rhizodeposition contribute to microaggregation. These and other traits, such as hemicellulose, soluble compounds, and high root branching index, favor macroaggregation. For stabilization by minerals and metals, those root traits promoting higher microbial activity: root nitrogen, hemicellulose and soluble compound concentrations are fundamental, while polyphenols, and litter Al and Mn also contribute to complexification and stabilization. Root depth distribution is the most important trait to control root C storage and stabilization in the subsoil; once roots have reached deeper soil layers, other traits, such as rhizodeposition and root chemistry, influence interaction with minerals and metals. Both mycorrhizal presence and root suberin promote SOC stabilization by means of all three mechanisms, indicating that these are important targets for continued work. Surprisingly, morphological traits commonly measured, namely specific root length and root diameter, poorly relate to stabilization mechanisms. Alternative traits such as chemical composition of the different root orders, root apex characteristics, quantity and quality of rhizodeposits as well as mycorrhizal fungal traits, should be further investigated. For future research, this review highlights the need to evaluate root decomposition and root-C stabilization concomitantly over the long-term, considering simultaneously root litter quality, estimated by root traits, the microbial products and properties of the soil matrix. The information accrued in this review can be used to evaluate the potential of plant species and cultivars to promote SOM stabilization, based on their root traits. Highlights: We identified 18 root traits influencing three soil organic matter stabilization mechanisms. Chemical traits reducing root recalcitrance promote interactions with mineral surfaces. Mycorrhizae and root suberin concentration are important to the three mechanisms. Specific root length and root diameter poorly relate to stabilization mechanisms. Root depth distribution is the most important trait to control root C stabilization in subsoil.